Application of metabolomics to decipher the role of bioactive compounds in plant and animal foods. (August 2022) - Munekata, Paulo E.S.; Pateiro, Mirian; Rocchetti, Gabriele; Domínguez, Rubén; Rocha, João M.; Lorenzo, José M.
Abstract : The consumption of foods characterized by a wide bioactive-compound profile has been associated with improved health status and reduced risk of developing diseases. Owing to the complexity of food production (e.g. crops and farmed animals), processing (e.g. fermentation), and shelf life (e.g. lipid or protein oxidation), a more comprehensive and holistic analysis is necessary to investigate the intricate metabolic pathways and metabolites involved with or displaying a biological activity. Accordingly, untargeted metabolomics analysis can provide crucial knowledge to support the selection of key metabolites and metabolic pathways to produce foods from animals and crops with a functional value. This short review aims to provide an overview of the applications of metabolomic analysis to screen bioactive compounds in both animal- and plant-based foods. Highlights: Metabolomics is essential to develop new strategies to produce functional foods. Quality control of polyphenols in tea production can be improved with metabolomics. Advances in poultry production with functional feeds are supported by metabolomics. Metabolomics in glucosinolate-rich foods revealed contrasting concerns about quality.